ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA BANGUN DATAR SEGIEMPAT DITINJAU DARI KEMAMPUAN PEMECAHAN MASALAH MATEMATIK UNTUK SISWA KELAS VII - anggraeni ratna sari; Usman Aripin (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This research seeks to explore and reveal students' mathematical problem solving abilities by analyzing student answers. The research subjects were seventh grade students taken from a public junior high school in Purwakarta Regency. The results of the study show that students' mathematical problem solving ability is still very weak and far to be complete even though the level of difficulty of the instrument is in the medium category. In general, the ability of these study subjects in mathematical problem solving is still below 50%. It is time for teachers to apply problem-based learning, in addition to conventional learning models, to provide opportunities and experiences for students to see and experience mathematical problem solving in the classroom. This qualitative study exposes students' responses in dealing with story questions in a rectangular building material. In addition the students are given the questions shown to reveal whether the students are using a systematic solution or can answer directly without a sequence, judging by the ability to solve mathematical problems. There were 6 heterogeneous students who were the subjects in this study. Based on the analysis that has been done, the results obtained are (1) students answer the problem is not systematic, (2) lack of understanding of the sequence of problem solving, (3) students are too hasty in doing math problems.